About one Problem of Analysis and Control in Systems with Distributed Parameters on the Example of Oil Fields - Suvonov Olim Omonovich (Genius Journals, 2022)
The paper considers the solution of the problem of optimal control of systems with distributed parameters, described by partial differential equations of elliptic type, as applied to oil fields. A qualitative analysis of the states of the system has been carried out by solving a boundary value problem in the class of generalized functions.
Keywords: System; distributed parameter; differential equation